The Influence of Financial Recording Systems on the Business Performance of Culinary MSMEs in Harjosari I Subdistrict, Medan Amplas - Nova Azahra; Sri Murniyanti; Muhammad Rizaldy Wibowo; Rukmini Rukmini (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
This study aims to evaluate the financial recording system implemented by Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector, and analyze its impact on business performance. MSMEs are a very dynamic sector and contribute significantly to the national economy, but many of them do not yet have an adequate financial recording system. Good financial recording is key in business decision making, budget planning, and profitability assessment. The population in this study were 370 culinary MSMEs in Harjosari I Village. The research sample was taken at 20%, namely 74 respondents. The study used a quantitative approach with a survey method through the distribution of questionnaires to 74 culinary MSMEs in Harjosari I Village, Medan Amplas. Data analysis was carried out using simple linear regression to see the relationship between the quality of the financial recording system as an independent variable and business performance as a dependent variable. The results showed that the better the financial recording system, the better the business performance, this can be shown by the regression equation, Y = 1.395 + 0.308 + e. The research results indicate that improving accounting literacy and the use of digital technologies, such as MSME bookkeeping applications, are essential. The involvement of local governments and financial institutions is crucial in educating and facilitating digital-based bookkeeping systems for culinary MSMEs to enhance their competitiveness and business sustainability.